Santri’s Multi-Track Diplomacy In Promoting The Islam Nusantara Identity To Global - Maulana, Ana (Universitas Nahdlatul Ulama Surabaya, 2023)
Prior to the 1961 Vienna Statute, only state actors were allowed to engage in diplomatic activities; however, non-state actors, including private citizens, are now included as well. This is, of course, based on several factors, starting from the flow of globalization to the role of the state, which is still unable to resolve certain issues, especially in the realm of peace advocacy. Of the many non-state actors involved in the practice of modern diplomacy, one of them is the individual actor, namely santri. Santri, in this case, has great potential and opportunities to become an actor in the world of diplomacy, especially in spreading peace advocacy. This condition can be seen through the historical record of santri, which has produced many peace-oriented movements. The dissemination of advocacy values also does not forget to highlight the characteristics of the Islam Nusantara identity, which is tolerant, friendly, and inclusive. In this regard, this research aims to explain the role of santri as diplomatic actor, especially in multi-track diplomacy to promote the Islamic values of Nusantara. The results of this research also prove that the role of santri in the realm of diplomacy is very broad and can be carried out through various multi-track diplomatic activities, ranging from inter-religious dialogue and santri exchange programs to the use of media platforms for da'wah media, which have become part of the form of novel diplomacy. In addition, to support this research, the author utilizes a qualitative research framework through the use of descriptive analysis methods and historical methods to obtain secondary data, based on internet-based research technique.